Medium-scale livestock farms in Asia’s rapidly transforming food systems - Ebata, Ayako; Belton, Ben (International Food Policy Research Institute, 2024)
Academic and policy debates on agriculture emphasize a bimodal typology of ‘small-scale’ and ‘large-scale’ farms. In this article, we draw attention to the role and distinct characteristics of medium-scale monogastric livestock farms in the Global South, drawing on an empirically grounded typology of scale that incorporates three linked components: (1) Social and economic organization of production; (2) Technological choice and environmental impacts, and; (3) Food system linkages and spillovers. We review national livestock sector policy documents from three Asian countries - Bangladesh, Myanmar, and Vietnam - with reference to the typology, and compare assumptions embedded in the policies with the characteristics of farm scale revealed by the typology. Our analysis indicates that current policy goals are not well aligned with the characteristics of medium-scale livestock farming in the region. This disconnect presents a missed opportunity to enhance the livestock sector’s contributions to rural economies, nutrition security, food safety, and environmental performance. We conclude with examples of how policies could maintain and enhance medium-scale monogastriclivestock farms’ contributions to sustainable intensification, public health, and livelihoods.